Neutrophil Extracellular Traps Drive Endothelial-to-Mesenchymal Transition. Issue 7 (July 2017) - Pieterse, Elmar; Rother, Nils; Garsen, Marjolein; Hofstra, Julia M.; Satchell, Simon C.; Hoffmann, Markus; Loeven, Markus A.; Knaapen, Hanneke K.; van der Heijden, Olivier W.H.; Berden, Jo H.M.; Hilbrands, Luuk B.; van der Vlag, Johan
Abstract : Objective—: An excessive release and impaired degradation of neutrophil extracellular traps (NETs) leads to the continuous exposure of NETs to the endothelium in a variety of hematologic and autoimmune disorders, including lupus nephritis. This study aims to unravel the mechanisms through which NETs jeopardize vascular integrity. Approach and Results—: Microvascular and macrovascular endothelial cells were exposed to NETs, and subsequent effects on endothelial integrity and function were determined in vitro and in vivo. We found that endothelial cells have a limited capacity to internalize NETs via the receptor for advanced glycation endproducts. An overflow of the phagocytic capacity of endothelial cells for NETs resulted in the persistent extracellular presence of NETs, which rapidly altered endothelial cell–cell contacts and induced vascular leakage and transendothelial albumin passage through elastase-mediated proteolysis of the intercellular junction protein VE-cadherin. Furthermore, NET-associated elastase promoted the nuclear translocation of junctional β-catenin and induced endothelial-to-mesenchymal transition in cultured endothelial cells. In vivo, NETs could be identified in kidney samples of diseased MRL/lpr mice and patients with lupus nephritis, in whom the glomerular presence of NETs correlated with the severity of proteinuria and with glomerular endothelial-to-mesenchymal transition. Conclusions—: These results indicate that an excess of NETs exceeds the phagocytic capacity of endothelial cells for NETs and promotes vascular leakage and endothelial-to-mesenchymal transition through the degradation of VE-cadherin and the subsequent activation of β-catenin signaling. Our data designate NET-associated elastase as a potential therapeutic target in the prevention of endothelial alterations in diseases characterized by aberrant NET release. Abstract : Supplemental Digital Content is available in the text.